Description of three new species of Glossogobius from Australia and New Guinea - Hoese, Douglass F.; Allen, Gerald R. (Zootaxa, 2009)
The present paper describes two new species of the gobiid fish genus Glossogobius from southern New Guinea and a third related species from northeastern Australia. All three species are restricted to a small number of river systems. Glossogobius bellendenensis, sp. nov. is distinctive in having reduced predorsal scales and fin-ray counts and mental frenum shape. It is restricted to relatively clear water rivers of northeastern Queensland. The closely related, Glossogobius muscorum sp. nov. is also distinctive in reduced predorsal scales and fin-ray count and is found only in the Fly River system of New Guinea. Glossogobius robertsi sp. nov. is distinctive in fin-ray and scale counts and is found in the Fly River in Papua New Guinea and possibly in a river in Papua close to the Fly River. That species has been confused with Glossogobius giuris, which generally occurs in lower reaches of the river.